Incarceration history is associated with HIV infection among community-recruited people who inject drugs in Europe: A propensity-score matched analysis of cross-sectional studies - Uusküla, Anneli; Rannap, Jürgen; Weijler, Lisa; Abagiu, Adrian; Arendt, Vic; Barrio, Gregorio; Barros, Henrique; Brummer-Korvenkontio, Henrikki; Casabona, Jordi; Croes, Esther; Jarlais, Don Des; Seguin-Devaux, Carole; et al. (Addiction (Abingdon, England), 2023)
AIMS: We measured the association between a history of incarceration and HIV positivity among people who inject drugs (PWID) across Europe. DESIGN, SETTING AND PARTICIPANTS: This was a cross-sectional, multi-site, multi-year propensity-score matched analysis conducted in Europe. Participants comprised community-recruited PWID who reported a recent injection (within the last 12 months). MEASUREMENTS: Data on incarceration history, demographics, substance use, sexual behavior and harm reduction service use originated from cross-sectional studies among PWID in Europe. Our primary outcome was HIV status. Generalized linear mixed models and propensity-score matching were used to compare HIV status between ever- and never-incarcerated PWID. FINDINGS: Among 43 807 PWID from 82 studies surveyed (in 22 sites and 13 countries), 58.7% reported having ever been in prison and 7.16% (n = 3099) tested HIV-positive. Incarceration was associated with 30% higher odds of HIV infection [adjusted odds ratio (aOR) = 1.32, 95% confidence interval (CI) = 1.09-1.59]; the association between a history of incarceration and HIV infection was strongest among PWID, with the lowest estimated propensity-score for having a history of incarceration (aOR = 1.78, 95% CI = 1.47-2.16). Additionally, mainly injecting cocaine and/or opioids (aOR = 2.16, 95% CI = 1.33-3.53), increased duration of injecting drugs (per 8 years aOR = 1.31, 95% CI = 1.16-1.48), ever sharing needles/syringes (aOR = 1.91, 95% CI = 1.59-2.28) and increased income inequality among the general population (measured by the Gini index, aOR = 1.34, 95% CI = 1.18-1.51) were associated with a higher odds of HIV infection. Older age (per 8 years aOR = 0.84, 95% CI = 0.76-0.94), male sex (aOR = 0.77, 95% CI = 0.65-0.91) and reporting pharmacies as the main source of clean syringes (aOR = 0.72, 95% CI = 0.59-0.88) were associated with lower odds of HIV positivity. CONCLUSIONS: A history of incarceration appears to be independently associated with HIV infection among people who inject drugs (PWID) in Europe, with a stronger effect among PWID with lower probability of incarceration.
Keywords: HIV; uživatelé drog; Cross-Sectional Studies; Male; HIV Infections; intravenózní abúzus drog; HIV séropozitivita; Europe; prison; injection drug use; mužské pohlaví; incarceration; Drug Users; Substance Abuse, Intravenous; PWID; Propensity Score; HIV infekce; tendenční skóre; Evropa; lidé; Humans; průřezové studie; HIV Seropositivity